Complete genome sequence of Cellulophaga lytica type strain (LIM-21(T)) - Pati, Amrita (Michigan State University, 2011)
Cellulophaga lytica (Lewin 1969) Johansen et al. 1999 is the type species of the genus Cellulophaga, which belongs to the family Flavobacteriaceae within the phylum 'Bacteroidetes' and was isolated from marine beach mud in Limon, Costa Rica. The species is of biotechnological interest because its members produce a wide range of extracellular enzymes capable of degrading proteins and polysaccharides. After the genome sequence of Cellulophaga algicola this is the second completed genome sequence of a member of the genus Cellulophaga. The 3,765,936 bp long genome with its 3,303 protein-coding and 55 RNA genes consists of one circular chromosome and is a part of the Genomic Encyclopedia of Bacteria and Archaea project.